Pelatihan Penerapan Harga Pokok Penjualan (HPP) Produk UMKM Pada Dusun Putak Loa Duri Ilir Kecamatan Loa Janan Kabupaten Kutai Karta Negara: Pengabdian - Sukirma; Akhmad Al Aidhi; Catur Kumala Dewi; Faizal Reza; Muhammad Maulana; Nurfitriani; Imam Nazarudin Latif; Andi Indrawati; Sunarto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Training on the application of Cost of Goods Sold (COGS) calculation was conducted in Dusun Putak Loa Duri Ilir, Loa Janan District, Kutai Kartanegara Regency, to improve the understanding of micro, small, and medium enterprises (MSMEs) and the tourism awareness group (Pokdarwis) in setting accurate and competitive product selling prices. This activity employed a participatory training method covering material on calculating raw material costs, indirect costs, and determining selling prices based on the desired profit margin. Participants gained insights into the importance of COGS in preventing business losses, estimating profits, and remaining competitive in the market. The results indicated an increase in participants’ ability to calculate COGS in detail and set selling prices aligned with production costs. This training is expected to serve as a foundation for sustainable business development and enhance the competitiveness of local products in the market.